Pelatihan Produksi Kerajinan Souvenir dari Kayu Lokal Berkualitas Rendah di Desa Huntu Selatan Kabupaten Bone Bolango: Training on Producing Souvenir Crafts Using Low Quality Local Wood in Huntu Selatan Village, Bone Bolango Regency - Sudana, I Wayan; Rahmatiah, Rahmatiah; Mohamad, Isnawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Wood is one of Gorontalo's local natural resources needed for various uses. However, only a few of these types of wood are naturally high quality, while most are low quality and, therefore, need to be more utilized. This service activity aims to utilize these low-quality local wood in various souvenir products through collaboration with the local community as partners. Implementation of activities uses participatory methods in the form of practical training through the stages: socialization and knowledge provision, provision of tools and materials, production process training, and finishing process training. The results are increased knowledge and skills of partners in producing various souvenirs from low-quality local wood, success in providing adequate tools and raw materials (low-quality local wood) to support production performance, partners succeeded in producing ten types of souvenirs by applying various finishing patterns, according to the models offered with a similarity level of 90%. With these results, partners become more productive and able to produce regularly, and their business is believed to continue to develop sustainably. This way, various low-quality local wood types from Gorontalo can be utilized optimally.